Basal ganglia hemorrhagic ablation associated with temporary suppression of obsessive-compulsive symptoms - Yaryura-Tobias,José A (2003)
Currently, basal ganglia (BG) are considered regulators of motor and emotional activity. It's operationality encompass Obsessive Compulsive Disorder (OCD). The case of a patient suffering with severe OCD is described of note, his symptoms disappeared following a hemorrhage of the left BG. However, once the hemorrhage was reabsorbed his symptoms returned. It is possible that lesions affecting cerebral OCD association circuits may influence the evolution of obsessive-compulsive symptoms.